Hot Water Blanching Pre-Treatments: Enhancing Drying of Seaweeds (Kappaphycus alvarezii S.) - Del Rosario, Eric Zamora; Mateo, Wendy (Open Science Journal, 2019)
It is really important to dry seaweeds in a shorter drying time without affecting its quality. Thus, this research aimed to investigate the effect of the application of hot water blanching pre-treatments on the drying rate, sensory, and nutritional attributes of seaweed (Kappaphycus Alvarezii, S.). Seaweed samples were blanched (88oC) at 5, 15 and 30 seconds duration and dried using solar glass dryer and heated air mechanical dryer. All samples were replicated three times. Complete Randomized Design (CRD) was used in both dryers and T-Test in comparing between dryers. Simple cost analysis was also performed to assess the annual cost and custom rate of using two methods of drying. It revealed that in heated air mechanical dryer, samples blanched for 5 and 15 seconds dry faster (8 hours). In solar glass dryer, seaweed samples blanched at 5 seconds dry earlier (32.67 hours). Results imply that hot water blanching affects drying time in drying seaweeds and hot water blanching pre-treatments increased drying rate at the initial hour of drying. It verified that models fitted show good predicting capacity and reveals a good correlation coefficient. Hot water blanching pre-treatments and types of dryers did not significantly affect the total ash contents of the seaweed powder, while in crude protein levels, it revealed that hot water blanching pre-treatment was not significant within the dryers but significantly different between drying methods. Moreover, pre-treatments undergone within the dryer were significantly different in crude fiber levels but insignificant in comparison between dryers. It also implied that the color of the seaweed powder dried in solar glass dryer was preferred by panels and all seaweed samples dried using heated air mechanical dryer turned to dark color. Results revealed that hot water blanching pre-treatments and types of dryer do not affect the texture and odor preference of the panels and general acceptability scores of the seaweed powder were insignificantly different within dryers. It also showed that using solar glass dryer and heated air mechanical dryer, it is profitable to blanch the seaweeds before drying.